Total and marketable fruit yield of strawberry plants grown under different levels of nitrogen fertility and inoculated with Azospirillum brasilense REC3 = Rendimiento frutal total y comercial de plantas de frutillas cultivadas bajo diferentes niveles de fertilidad nitrogenada e inoculadas con Azospirillum brasilense REC3 - Lovaisa, Nadia Carolina; Guerrero Molina, María Fernanda; Delaporte Quintana, Paola Adriana Georgina; Salazar, Sergio Miguel (Facultad de Agronomía y Zootecnia, Universidad Nacional de Tucumán, 2019)
The aim of this work was to evaluate the agronomic response of strawberry plants (Fragaria ananassa Duch.) inoculated with Azospirillum brasilense as a biotechnological alternative to reduce or complement the plant nitrogen-fertilization under field conditions. The field trial was carried out in the province of Tucumán, Argentina, inoculating or not strawberry plants (cv. ‘Camino Real’) with A. brasilense REC3 and applying or not nitrogenfertilization. Treatments consisted in plants cultivated under different nitrogen fertilization (0%, 50%, 100%) with or without bacterial inoculation. The variables assessed were: SPAD relative values, total and marketable fruit yield, and growth index. As a result, it was observed that A. brasilense REC3 contributed positively to the nitrogennutrition of strawberry plants growing at field conditions, expressed in the values of the variables assessed.